Seasonal yield, leaf area index and light interception of alfalfa cultivars under grazing - Ferragine, María del Carmen; Pedreira, Carlos Guilherme Silveira; Otani, Lyssa; Tonato, Felipe (Pesquisa Agropecuaria Brasileira, 2004)
Grazed alfalfa (Medicago sativa L.) may reduce feeding costs of ruminant livestock but the agronomic performance of cultivars under grazing in Brazil is little known. The objective of this work was to evaluate the effect of the grazing method on herbage accumulation (HA), leaf area index (LAI) and light interception (LI) of five alfalfa cultivars over 295 days in Piracicaba, SP, Brazil. The trial was set up in a randomized complete block design and a split-plot arrangement (methods in the whole-plots and cultivars in the subplots). ABT-805 was the highest yielding entry under both continuous (26,600 kg ha-1 year-1) and rotational (18,000 kg ha-1 year-1) stocking. It also had the highest mean LAI (2.1) and LI (53%) under rotational stocking. Alfagraze, one of the lowest yielding cultivars under rotational stocking (13,300 kg-1 ha year-1) sustained similar total forage accumulation to that of ABT-805 under continuous stocking (26,300 kg ha-1 year-1), with a mean LI of 47% and mean LAI between 1.1 and 1.8 for continuous and rotational stocking, respectively. Pioneer 5432 had a mean LI of 49%, total seasonal herbage accumulation of 24,300 and 15,300 kg ha-1 year-1, mean LAI of 0.98 and 1.76, and mean survival of 7.3 and 24.9% under continuous and rotational stocking, respectively. Crioula and CUF-101 show a more pronounced seasonal growth under both grazing methods. ABT-805 is the best entry under grazing and under local conditions.